Transmission of recombinant enterovirus A76 (EV-A76) in Xinjiang Uighur autonomous region of China - Li, Xiaolei; Lu, Huanhuan; Sun, Qiang; Zheng, Peng; Zhang, Bo; Cui, Hui; Tang, Haishu; Zhao, Hehe; Liu, Ying; Jiang, Jie; Xiao, Jinbo; Zhang, Yong (Emerging microbes & infections, 2023)
Enterovirus 76 (EV-A76) is a serotype of enterovirus A and has been rarely reported. In this paper, we present the genetic characteristics of 15 EV-A76 isolates reported to circulate in the Xinjiang Uighur autonomous region of China in 2011. Sequence analysis revealed that all Chinese EV-A76 isolates had high similarity (> 98.3%) in the VP1 region, and five Chinese EV-A76 isolates were selected for whole genome sequencing based on VP1 nucleotide divergence. Similarity plots and boot-scanning analyses revealed frequent intertypic recombination in the nonstructural region of the EV-A76 isolate, as found with the EV-A89 donor sequence (also isolated in Xinjiang). The breakpoint of recombination is around nucleotide 3960, and the recombinant fragments covered part 2C and all P3 regions. This study increases publicly available EV-A76 nucleotide sequence and further our understanding EV-A76 molecular epidemiology.